The ethnomusicology under a contemporary look - Silva, Jonathan Lambert (Laboratório Editorial Faculdade de Ciências e Letras, 2018)
The present article aim to discuss the development of the ethnomusicology area through works of Tiago de Oliveira Pinto and Rafael José de Menezes Bastos focusing the anthropologic look that permeate the contemporary discussions about the global system and the local culture.